A comparative study on efficacy and safety profile of risperidone and iloperidone in patients of schizophrenia: randomized controlled study - Acharya, Swathi; Srinivasa, V.; Kotresh, S.; Mulimani, Sharanappa; Bhat, Anithraj; Bhat, Manohar (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Antipsychotics are most commonly used as first line therapy for schizophrenia. Treatment with antipsychotics is marked by poor compliance, drug discontinuation and frequent switching attributable to lack of efficacy of recently introduced atypical antipsychotics. The objectives of this study was to compare the efficacy and safety profile of risperidone, most commonly used drug with iloperidone,a recently introduced antipsychotic. Methods: In this prospective, randomized open label 6-week study, 80 patients with diagnosis of Schizophrenia were randomized to two groups to receive either risperidone (4-8 mg) or iloperidone (6-24 mg). Their efficacy was assessed using reduction in PANSS score and safety profile was assessed by monitoring the adverse effects during follow-up visits at 2, 4, 6 weeks. Results: Efficacy parameter, PANSS score showed significant reduction in both groups as compared to baseline values after 6 weeks. But there were no significant differences between two groups. The safety profile assessed by comparison of adverse effects showed statistically significant differences between the groups (<0.01). Conclusions: Iloperidone with better extrapyramidal side effect profile and equivalent efficacy can be considered as good alternative to risperidone in schizophrenia treatment.